Morphogenetic Identification of a New Record Condica capensis (Lepidoptera: Noctuidae) in Yunnan, China - Pengfan Qian; Jiayin Fan; Xiaoyuan Zhang; Minfang Zeng; Xiaolong Han; Yonghe Li; Xulu Luo (Insects, 2025)
Condica capensis (Lepidoptera: Noctuidae), a newly identified pest in Yunnan Province, China, poses a threat to safflower crops. Discovered in Nanhua County in November 2023, the pest damages safflower at multiple life stages, especially during its larval stage, when it feeds on leaves, tender stems, and flower filaments, sometimes causing the entire plant to die. Morphological and molecular analyses, including mitochondrial cytochrome C oxidase I (COI) gene sequencing, confirmed its identity as C. capensis, a new species record for Yunnan. The study also documented the pest’s life cycle, reproductive behavior, and natural enemies, highlighting the potential for biological control using parasitic wasps such as Cotesia sp. This research emphasizes the need for accurate pest identification and monitoring to develop effective, sustainable pest management strategies. As safflower cultivation grows in Yunnan, managing C. capensis is critical to safeguarding local agriculture and preventing broader agricultural threats.